A QUANTITATIVE ASSESSMENT OF THE PRICE INFLUENCE ON CONSUMER PURCHASE DECISIONS FOR ELECTRONIC GOODS - Azilah, Eva; Arif Musthofa, M.; Yatima, Khusnul; Wandi; Nisa Munamah, Anatun (Program Studi Ekonomi Syariah, Universitas Pangeran Diponegoro Nganjuk, 2025)
As time goes by, human integrity is increasing and becoming more varied. One of the needs is electronic goods. However, to get this, of course there is an exchange rate that must be paid to get an item. Price is one of the factors that influences consumer decisions, because price is also sometimes a consideration for many people. It is not uncommon for valuable electronic items to be set at high prices because sometimes they look at the quality and usefulness of the item. This research aims to determine the effect of price on consumer decisions when purchasing electronic goods at the French Jaya Muara Sabak Barat store. This type of research is quantitative, the population is 134 people, the sample was determined using purposive sampling, namely the sample was determined using the Slovin method, the sample size was 100 people. The data analysis technique uses simple linear regression analysis using the spps 25 program. The results of this research state that the prices offered by the France Jaya Store have a significant influence on consumer decisions when purchasing electronic goods at the France Jaya Store. The coefficient of determination value which is the result of r square is 0.839. These results show that 83.9% of the influence of the price variable (x) on consumer decisions (y). Meanwhile, the remaining 16.1% of the price value is influenced by other variables that are not yet in this research.